REVIEWING FRAMEWORK OF CURRICULUM IMPLEMENTATION: ASEAN CONTEXT - Run, Netra (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
The framework of curriculum implementation had been argued to be complex and vague since it was hard to identify how, what, and where to begin. This paper aims to review the framework of curriculum implementation in the ASEAN context on how the curriculum is formulated, prototyped, and implemented. Employing the integrative review approach of the conventional review paper, 27 articles (22 primary data and 5 secondary data) were collected from Google Scholar to form themes, sub-themes, and codes. The findings indicated that the curriculum is implemented into 5 main circles: (1) the planning and consultation circle is categorized into 5 elements: identifying core values and areas of knowledge, key knowledge and skills for learners, basic and relevant resources, practitioners and relevant stakeholders, and reviewing plan and consultation; (2) designing and development circle is classified into 3 elements: contents, pedagogies, and assessments; (3) the trailing and prototyping circle is covered by 3 elements: contents, syllabuses, and resources; (4) the implementation and communication circle is followed by 3 elements: gathering information, reflection, and possible changes; and (5) post-implementation and evaluation is classified into 4 elements: assessment and feedback, reflection and evaluation, making changes, and post-implementation and updates.